2007
DOI: 10.1093/ndt/gfm066
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil in induction and maintenance therapy of severe lupus nephritis: a meta-analysis of randomized controlled trials

Abstract: MMF has higher efficacy in inducing remission in severe LN than pulsed intravenous therapy with CYC. Induction therapy with MMF is also associated with fewer side effects than induction therapy with CYC. Compared with AZA, MMF also is an alternative for maintenance therapy of severe LN without significant difference in the prognosis or risks of amenorrhoea and herpes zoster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
1
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(83 citation statements)
references
References 39 publications
2
74
1
6
Order By: Relevance
“…In a recent experiment on the effect of aldosterone blockade on the development and progression of glomerulonephritis in a murine model of lupus, spironolactone significantly reduces the incidence of nephrotic range proteinuria and, on histology, showed far less severe glomerular injury (no crescents, diminished overall cellularity, and less prominent deposits in the capillary loops and mesangium) compared with controls. 16 The investigators found significant differences in levels of anti-ssDNA and anti-dsDNA antibodies between control mice and mice treated with spironolactone by 36 ISN class III, focal lupus nephritis, is defined as focal segmental and/or global endocapillary and/or extracapillary glomerulonephritis affecting Ͻ50% of the sampled glomeruli. ISN class IV, diffuse lupus nephritis, has diffuse segmental and/or global endocapillary and/or extracapillary glomerulonephritis affecting Ն50% of glomeruli.…”
Section: Conservative Nonimmunomodulatory Therapy Is Appropriate Formentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent experiment on the effect of aldosterone blockade on the development and progression of glomerulonephritis in a murine model of lupus, spironolactone significantly reduces the incidence of nephrotic range proteinuria and, on histology, showed far less severe glomerular injury (no crescents, diminished overall cellularity, and less prominent deposits in the capillary loops and mesangium) compared with controls. 16 The investigators found significant differences in levels of anti-ssDNA and anti-dsDNA antibodies between control mice and mice treated with spironolactone by 36 ISN class III, focal lupus nephritis, is defined as focal segmental and/or global endocapillary and/or extracapillary glomerulonephritis affecting Ͻ50% of the sampled glomeruli. ISN class IV, diffuse lupus nephritis, has diffuse segmental and/or global endocapillary and/or extracapillary glomerulonephritis affecting Ն50% of glomeruli.…”
Section: Conservative Nonimmunomodulatory Therapy Is Appropriate Formentioning
confidence: 99%
“…A number of meta-analyses unequivocally favor the additional benefit of using an immunosuppressive agent (or agents) during the maintenance phase of lupus nephritis therapy. 33,36,27 Given the risk for long-term toxicities with such agents, as well as their potential effect on fertility and risk for teratogenicity, the selection and dosage of maintenance therapy is an important and modifiable choice that doctor and patient should make together.…”
Section: Maintenance Phase Treatment Of Proliferative Lupus Nephritismentioning
confidence: 99%
“…There is a paucity of published data regarding the role of mycophenolate mofetil in VZV reactivation among patients with SLE, although it has been implicated in the development of VZV infection among transplant recipients. A recent meta-analysis of randomized controlled trials of mycophenolate mofetil for lupus nephritis found that rates of VZV reactivation were similar among patients treated with cyclophosphamide, those treated with azathioprine, and those treated with mycophenolate mofetile (18).…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Several small trials showed that MMF was comparable to CYP in the treatment of proliferative LN. 57,58 Ginzler et al conducted a 24-week randomized, open-label, non-inferiority trial comparing oral MMF with monthly intravenous CYP as induction therapy. They showed that MMF was more effective in inducing remission of lupus nephritis and had a better safety profile.…”
Section: Mycophenolate Mofetilmentioning
confidence: 99%